2013
DOI: 10.1007/s00296-013-2822-0
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin in rheumatoid arthritis: the addition to methotrexate and low-dose methylprednisolone induces a significant additive value—a 24-month single-blind pilot study

Abstract: sixteen patients treated for 24 months with MTX 10-15 mg i.m. weekly and MP 4-6 mg daily. CM group: sixteen patients treated with MTX 10-15 mg i.m. weekly and MP 4-6 mg daily for 24 months; CM therapy added in the first month (500 mg twice a day for the first 15 days followed by 500 mg a day for the remaining 15 days). Evaluation of the improvement following ACR criteria was performed at months 1 (primary endpoint), 3 and 6. Patients were furthermore observed after 12, 18 and 24 months from the study beginning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Saviola et al (2) reported that CAM (500 mg twice per day for the first 10 days, followed by 250 mg twice per day for the long term) could be beneficial in RA patients who were not responsive to, or could not tolerate diseasemodifying antirheumatic drugs (DMARDs). They also reported the efficacy of the addition of CAM (500 mg twice per day for the first 15 days, followed by 500 mg per day for the remaining 15 days) to MTX and low-dose methyl-PSL in active RA (3). In the present case, a patient who had already received PSL was treated with CAM.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Saviola et al (2) reported that CAM (500 mg twice per day for the first 10 days, followed by 250 mg twice per day for the long term) could be beneficial in RA patients who were not responsive to, or could not tolerate diseasemodifying antirheumatic drugs (DMARDs). They also reported the efficacy of the addition of CAM (500 mg twice per day for the first 15 days, followed by 500 mg per day for the remaining 15 days) to MTX and low-dose methyl-PSL in active RA (3). In the present case, a patient who had already received PSL was treated with CAM.…”
Section: Discussionmentioning
confidence: 63%
“…Regarding anti-inflammatory effects, successful treatments with Mac for diffuse panbronchiolitis, cystic fibrosis, chronic obstructive pulmonary disease, and bronchial asthma have been reported. Similarly, several recent studies have reported successful treatment of rheumatoid arthritis (RA) with CAM (1)(2)(3). RA is an inflammatory disease in which proinflammatory cytokines such as tumor necrosis factor (TNF)-α are associated with clinical features.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding anti-inflammatory effects, successful treatments with Macs for diffuse panbronchiolitis, cystic fibrosis, chronic obstructive pulmonary disease, and bronchial asthma have been reported. Similarly, several recent studies have reported successful treatment of rheumatoid arthritis (RA) using Macs as anti-inflammatory agents [1][2][3][4]. We also report herein two cases of uncontrolled RA, accompanied by hepatitis B and pulmonary empyema, respectively, who were successfully treated using CAM in expectation of its anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 70%
“…Saviola et al [1] reported that CAM (500 mg twice a day for the first 10 days, followed by 250 mg twice a day for the long term) could be beneficial in RA patients who were not responsive to, or could not tolerate, disease-modifying antirheumatic drugs (DMARDs). They also reported the efficacy of adding CAM (500 mg twice per day for the first 15 days, followed by 500 mg/day for the remaining 15 days) to MTX and low-dose methyl-PSL in active RA [3]. Regarding RXM treatment for RA, Ogrendik [4] reported that treatment with RXM at 300 mg/day for 3 months improved DAS28.…”
Section: Case Reportsmentioning
confidence: 99%
“…This study showed that the addition of a 4-week clarithromycin cycle was efficacious in inducing the remission of the disease [50].…”
Section: Macrolide Antibioticsmentioning
confidence: 79%